Digital Transformation and Employee Competence : The Impact of Internal Brand Engagement in Higher Education - Urooj, Ahmed; Mahani, Mohammad Abdu Shakur; Sharizal, Hashim; Rukhsar, Ahmed (Human Resource Management Academic Research Society, 2024)
This research examines the impact of digital enablement on employee competence, mediated by internal brand engagement, within higher education institutions in Pakistan. Internal brand engagement, encompassing communication, training, and leadership, is posited to play a critical role in enhancing the effectiveness of digital enablement initiatives. Utilizing a sample of 541 employees, Smart PLS was employed to test the conceptual framework. The findings reveal that digital enablement significantly enhances internal brand engagement, which in turn positively influences employee competence. The study confirms that effective communication, robust training programs, and strong leadership are essential for maximizing the benefits of digital tools and technologies. All hypotheses were accepted, indicating the robustness of the proposed model. This research contributes to the existing literature by integrating digital enablement with internal brand engagement to provide a comprehensive understanding of the factors that enhance employee competence. The results offer valuable insights for higher education administrators seeking to improve employee performance and engagement through targeted digital and internal brand strategies. By addressing the interaction between digital enablement and internal brand engagement, this study highlights the strategic importance of fostering a supportive and cohesive work environment to sustain competitive advantage in the educational sector.